IDENTIFIKASI FUNGI DIVISI BASIDIOMYCOTA DI KAWASAN HUTAN ADAT BUKIT SELEBU KECAMATAN TABIR BARAT KABUPATEN MERANGIN - Kuniroh Kuniroh; Rozana Zuhri; Pitri Handayani (BIOCOLONY, 2022)
Fungus are one of the biodiversity that act as decomposers in forest ecosystems. The Bukit Selebu customary forest is a primary forest which is used as customary forest by the local community. In addition, in the Bukit Selebu customary forest, no one has yet conducted research. Therefore, it is necessary to1collect data on the types of mushrooms in the Bukit Selebu customary forest area. The purpose1of this study was to determine the types of fungi of the Basidiomycota Division in the Bukit Selebu customary forest area. This study used the roaming method, namely exploring to find mushrooms directly at the research location. Fungal identification was carried out in the field and at the Merangin University Biology Laboratory. During the observation of the types of mushrooms found in the field data records,Namely the substrate, color, fruit body shape and height. The results of this study obtained 14 species consisting of 4 orders and 4 families. Of the 4 different orders, the most dominant, namely from the order Polyprales, 8 species, namely Tremetes sp. Amauroderma sp. Fomitopsis sp. Earliella sp. Pcynoporus sp. Trichaptum sp. Polyporus sp. Genoderma sp. Order Agaricales 4 species namely Schizopyllum sp. Crepidotus sp. Collybia sp. Boletus sp. Order Auriculariales 1 species namely Auricularia sp. and the Hymenochaetales order has 1 species, namely Coltricia sp.